Carbon Trading or Carbon Tax? A Computable General Equilibrium–Based Study of Carbon Emission Reduction Policy in China - Shen, Jing; Zhao, Changheng (Frontiers in Energy Research, 2022)
To solve the environmental problems caused by climate change, the Paris Agreement urges China to accelerate the pace of CO2 emission reduction. Carbon trading and carbon tax have been considered the key instruments in reducing CO2 emissions. The focus of this article is not only to examine the impact of carbon trading and the carbon tax policy on China’s macroeconomy but also to study the “carbon trading–carbon tax” mixed policy and make a comparative analysis based on the computable general equilibrium (CGE) model. We found that the mixed policy is more favorable to China’s macroeconomy than a single carbon emission reduction policy and is conducive to improving people’s welfare. If a carbon tax is carried out, a relatively mild and low carbon tax rate should be adopted to achieve China’s carbon emission reduction goal and have a favorable impact on the macroeconomy. The main purpose of this article is to provide a theoretical basis and policy advices for the Chinese government in formulating innovative carbon reduction policies.